PELAYANAN PRIMA, KOMUNIKASI ANTARPRIBADI, GAYA KOMUNIKASI ACCOUNT REPRESENTATIVE, MOTIVASI, DAN KEPUASAN WAJIB PAJAK MEMBAYAR PAJAK - I Gede Dwi Adnyana (Jurnal Manajemen dan Bisnis, 2013)
The purpose of this study was to investigate and analyze: (1) the influence ofexcellent service towards the taxpayers motivation to pay taxes, (2) the effect ofinterpersonal communication to motivate taxpayers to pay taxes, (3) the influence ofAccount Representative communication styles towards the taxpayers’ motivation to paytaxes, (4) the influence of excellent service towards the satisfaction of taxpayers in payingtaxes, (5) the effect of interpersonal communication towards the satisfaction of thetaxpayers in paying taxes, (6) the effect of the communication styles of AccountRepresentative towards the satisfaction of the taxpayers in paying taxes, (7) the effect ofmotivation towards the satisfaction of the taxpayers in paying taxes.The research method used was a survey study, using purposive sampling with asample size of 152 people. The technique of the data analysis used was Structural EquationModeling (SEM).Based on the results of the study can be concluded as follows: excellent service hasa positive and significant impact on the motivation of taxpayers to pay tax of 0.360.Interpersonal communication has a positive and significant impact on the motivation of0.023. Communication style has a positive and significant impact on the motivation of0.745. Excellent service has a positive and significant impact on satisfaction of 0.548.Interpersonal communication has a positive and significant impact on satisfaction of0.237. which means the better interpersonal communication carried by AccountRepresentative, the higher the satisfaction of taxpayers in the Tax Office PratamaDenpasar Barat, and vice versa. Communication style has a positive and significant impacton satisfaction of 0.689 which means the better communication style carried by AccountRepresentative, the higher the satisfaction of taxpayers in the Tax Office PratamaDenpasar Barat, and vice versa, and motivation has a positive and significant impact onsatisfaction of 1.794, which means the higher the motivation, the higher the satisfaction oftaxpayers in the Tax Office Pratama Denpasar Barat, and vice versa.